Knowledge-Driven Multilingual Event Detection Using Cross-Lingual Subcategorization Frames - Mikelić Preradović, Nives (Array, 2013)
In this paper we present a knowledge-driven approach to multilingual event detection using a combination of lexico-syntactic patterns and semantic roles to build cross-lingual event frames, based on the meaning of the verb prefix and the relation of the prefixed verb to its syntactic arguments. We concentrate on SOURCE and GOAL roles, encoding adlative, ablative, intralocative and extralocative meaning in the event frames of five Indo-European languages: Croatian, English, German, Italian and Czech. The lexico-syntactic pattern for each frame was manually developed, covering directional meaning of Croatian prefixes OD-, DO-, IZ- and U-. Apart from the possibility to detect spatial (directional) information in five languages, results presented here suggest a possible approach to improve foreign language learning using a set of cross-lingual verb valency frames.